Workshop Academic Writing: Pemanfaatan Teknologi dalam Meningkatkan Kompetensi Penulisan Karya Ilmiah Mahasiswa - Shobri, Muwafiqus (PT. Cahya Edupreneur Indonesia, 2024)
This community service activity aims to improve the skills of students of the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) STAI Hasan Jufri Bawean in writing scientific papers according to academic standards. The approach used is the Service Learning (SL) method, which integrates theoretical and practical learning with the empowerment of technologies such as Mendeley, DeepL, Google Scholar, and Google Books. The results of the activity showed that students experienced a significant improvement in understanding the structure of IMRAD-based scientific writing, reference management, and the use of supporting technology. This training also encourages students to publish their scientific papers. In conclusion, this activity has succeeded in having a positive impact on students' academic skills and culture. It suggests the implementation of similar programs in a sustainable manner for wider results.